2020
DOI: 10.1093/tas/txaa163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis PB6 and/or chromium propionate supplementation on clinical health, growth performance, and carcass traits of high-risk cattle during the feedlot receiving and finishing periods1

Abstract: The study objective was to determine the effects of Bacillus subtilis PB6 and/or chromium propionate supplementation on health, growth performance, and carcass characteristics of high-risk beef cattle during a 56-d feedlot receiving period and the subsequent finishing period. Four truckload blocks of crossbred beef bulls (n=300) and steers (n=84; BW = 220 ± 16.2 kg) were sourced from regional auction markets and assigned randomly to treatments arranged in a 2 × 2 factorial. The generalized complete block desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…This is similar to what has been reported by Smock et al (2020a) who noted no improvements in cumulative growth performance responses in steers when B. subtilis PB6 was fed to high-stressed feeder steers. Alternatively, Smock et al (2020a) noted an improvement in ADG and DMI during the initial 56-d feedlot-receiving phase when B. subtilis PB6 was supplemented to high-stressed feeder steers. Estimated dietary NE based on growth performance was in close agreement with the expectation based on diet formulation ( P ≥ 0.46).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is similar to what has been reported by Smock et al (2020a) who noted no improvements in cumulative growth performance responses in steers when B. subtilis PB6 was fed to high-stressed feeder steers. Alternatively, Smock et al (2020a) noted an improvement in ADG and DMI during the initial 56-d feedlot-receiving phase when B. subtilis PB6 was supplemented to high-stressed feeder steers. Estimated dietary NE based on growth performance was in close agreement with the expectation based on diet formulation ( P ≥ 0.46).…”
Section: Resultssupporting
confidence: 91%
“…Finally, there were no treatment effects ( P ≥ 0.54) for the prevalence of abscessed livers in this experiment. These findings are very similar to Smock et al (2020a) , who indicated that the distribution of USDA YG and quality grade or condemned livers were not influenced by the supplementation of B. subtilis PB6 to finishing beef steers.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…By d 14, we saw a linear decrease in DMI as calves were processed beyond 6-h. Additionally, cattle were not allotted to their experimental pens until all calves had been processed at 48-h post-arrival. Each receiving pen provided free-choice hay and water, but no concentrate was provided until all cattle had been processed at 48-h. Much work has been done assessing how this time frame impacts the digestion and rumen function of cattle and their ability to adapt to the receiving diet ( Duff and Gaylean, 2007 ; Gilbery et al, 2007 ; Smock et al, 2020 ). Limited ruminal fermentative capacity (RFC) is a potential factor responsible for limited feed intake in cattle deprived of feed due to transport.…”
Section: Resultsmentioning
confidence: 99%
“…The 0.3 mg/kg diet resulted in the lowest BRD morbidity (7.5% vs. 25.9% for the control diet). Smock et al (2020) compared the effects of a Bacillus subtilis PB6 direct-fed microbial and 450 ppb chromium propionate or the combination of the two with a control diet in 384 bull and steer calves (220 kg BW) during a 56-d receiving period. The direct-fed microbial, alone or in combination with Cr, increased DMI for the receiving period compared with other treatments, which was associated with increased ADG.…”
Section: Introductionmentioning
confidence: 99%